(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was designed evaluate the structural morphology of palatal rugae in Kerala orthodontic subjects with varying Sagittal Skeletal Malocclusions. Pretreatment maxillary casts of 105 patients were analyzed for rugae patterns qualitatively and quantitatively using modified Thomas and Kotze classification. The data were statistically analyzed. According to the Fishers exact test, the most common type of rugae pattern in all the groups (Class I, Class II, and Class III) were observed to be wavy followed by curved. Skeletal Class III had the highest number of straight rugae 71.4% among the three groups which was statistically significant. Direction of rugal alignment was horizontal and droplet-shaped incisive papilla was identified among different skeletal dysplasia groups.Palatal ruage may serve as valuable indicators for population identification and help in facial reconstructions through their association with varying skeletal malocclusions.